Distal ExsA-Binding Site in Pseudomonas aeruginosa Type III Secretion System Promoters Is the Primary Determinant for Promoter-Specific Properties - Brutinel, Evan D; King, Jessica M; Marsden, Anne E; Yahr, Timothy L (Journal of Bacteriology, 2012)
Transcription of the Pseudomonas aeruginosa type III secretion system is controlled by ExsA, a member of the AraC/XylS family of regulators. Each ExsA-dependent promoter contains two adjacent binding sites for monomeric ExsA. The promoter-proximal site (binding site 1) consists of highly conserved GnC and TGnnA sequences that are individually recognized by the two helix-turn-helix (HTH) DNA-binding motifs of an ExsA monomer. While the GnC and TGnnA sequences are important for binding to site 1, the promoter-distal binding sites (site 2) lack obvious similarity among themselves or with binding site 1. In the present study, we demonstrate that site 2 in the PexsC promoter region contains a GnC sequence that is functionally equivalent to the GnC in site 1 and recognized by the first HTH motif of an ExsA monomer. Likewise, the second HTH interacts with an adenine residue in binding site 2. Although several candidate GnC sequences are also present in site 2 of the PexsD, PexoT, and PpcrG promoters, the GnC sequences were not required for ExsA-dependent transcription or ExsA binding. A comparison of hybrid promoters composed of binding site 2 from one promoter fused to binding site 1 derived from another promoter indicates that ExsA-binding affinity, promoter strength, and the degree of promoter bending are properties that are largely determined by binding site 2. Based on these data, we propose that the manner in which ExsA interacts with binding site 2 at the PexsC promoter is distinct from the interactions occurring at other promoters.